2013
DOI: 10.1186/1471-2393-13-106
|View full text |Cite
|
Sign up to set email alerts
|

Fetal head circumference, operative delivery, and fetal outcomes: a multi-ethnic population-based cohort study

Abstract: BackgroundOperative delivery procedures, such as primary cesarean section, vacuum-assisted, and forceps-assisted vaginal delivery increase maternal and fetal morbidity, and the cost of care. We evaluated whether large fetal head circumference (FHC) independently increases risk of such interventions, as well as fetal distress or low Apgar score, in anatomically normal infants.MethodsWe conducted a population-based retrospective cohort study using Washington State birth certificate data. We included singleton, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
(30 reference statements)
0
27
0
Order By: Relevance
“…In one hand, newborn death, uterine rupture and obstetric fistula are among complications with the saddest impact on a surviving primiparous woman and her family with regard to the pronatalist African culture. In the other hand, cephalopelvic disproportion due to generally contracted pelvis or large foetal head circumference is one of caesarean section indications in nulliparae and pregnant women aged less than 19 [17][18][19][20]; and this should also be the case in settings characterised by early marriages and lack of appropriate pregnancy monitoring. Besides, it is also known that external pelvimetry is nowadays controversial and no longer in favour with many obstetricians [21,22], now that new, more powerful diagnostic tools, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In one hand, newborn death, uterine rupture and obstetric fistula are among complications with the saddest impact on a surviving primiparous woman and her family with regard to the pronatalist African culture. In the other hand, cephalopelvic disproportion due to generally contracted pelvis or large foetal head circumference is one of caesarean section indications in nulliparae and pregnant women aged less than 19 [17][18][19][20]; and this should also be the case in settings characterised by early marriages and lack of appropriate pregnancy monitoring. Besides, it is also known that external pelvimetry is nowadays controversial and no longer in favour with many obstetricians [21,22], now that new, more powerful diagnostic tools, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the impact of head circumference on the odds of operative delivery in nulliparae; [6][7][8]10 rather focusing on estimated fetal weight. 11 The earlier studies showed that the odds of operative delivery and prolonged second stage of labor 6-8 increased as HC increased, and found as we did that infants of higher birth weight were less likely to show signs of fetal distress than smaller fetuses with similar HC 6 .…”
mentioning
confidence: 97%
“…the tension at the point of meeting of the human fetal head and the bipedal female pelvis, [1][2][3][4] but sparse attention has been paid in the obstetric literature to the impact of head circumference on obstetric outcomes. [5][6][7][8][9][10] The literature on problems of delivery in "big babies" focuses primarily on fetal size in terms of weight. [11][12][13][14] We queried how fetal head dimensions might impact the passage of the fetus through the birth canal and affect obstetric outcomes, primarily delivery mode.…”
mentioning
confidence: 99%
“…Several prior studies have used head circumference data obtained from the birth certificate to evaluate infant and maternal health outcomes (Krstev, Marinković, Simić, Kocev, & Bondy, 2013;Mujugira, Osoti, Deya, Hawes, & Phipps, 2013). To our knowledge, there is not a study available that has investigated the accuracy of birth certificate head circumference data.…”
mentioning
confidence: 99%